2014
DOI: 10.1136/thoraxjnl-2014-205956
|View full text |Cite
|
Sign up to set email alerts
|

Mortality trends in women and men with COPD in Ontario, Canada, 1996–2012

Abstract: Mortality in people with COPD has decreased; however, the decrease has been greater in men than in women. Public health interventions and medical care appear to be improving mortality in individuals with COPD but more research is needed to determine if they are benefiting both sexes equally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 21 publications
2
22
0
2
Order By: Relevance
“…A difference between sexes in the prevalence of COPD has been reported previously [20e22]. A sharp decline in male mortality from COPD compared with that in women and a narrowing in the sex gap have been described in Canada and Europe [20,23]. The reason for this may be that women with COPD appear to have earlier onset and a more rapid decline in lung function, despite similar cigarette exposure [21,22,24].…”
Section: Discussionmentioning
confidence: 68%
“…A difference between sexes in the prevalence of COPD has been reported previously [20e22]. A sharp decline in male mortality from COPD compared with that in women and a narrowing in the sex gap have been described in Canada and Europe [20,23]. The reason for this may be that women with COPD appear to have earlier onset and a more rapid decline in lung function, despite similar cigarette exposure [21,22,24].…”
Section: Discussionmentioning
confidence: 68%
“…This scenario has changed in recent years as there has been a steady increase in COPD prevalence and mortality rates in women. In the US, for example, the number of COPD-associated deaths in women has equaled or surpassed that in men (1), while in Canada, a longitudinal population study revealed a greater decrease in COPD-related mortality trends in men versus women (2). The increased prevalence of COPD among women is likely attributable to several factors including the increased rates of cigarette smoking observed in women during recent years, exposure to indoor air pollution (biomass) as well as increased occupational exposures as women take on previously male-dominated occupational roles related to risk exposure (3).…”
Section: Introductionmentioning
confidence: 99%
“…26 This case definition was found to have a sensitivity and specificity of 85.0% and 78.4%, respectively, for identifying COPD with Ontario's health administrative records and has been used extensively to study outcomes among people with COPD. 27,28…”
Section: Discussionmentioning
confidence: 99%